The Effect Of Behavior Contracts On The Prevention Of Procrastination Of Elementary School Students - Endriani, Citra Rista; Yuliyanto, Aan; Fujiarti, Ari; Cunayah, Cunayah; Mubarok, Rizqi; Wandi, Wandi (International Conference on Elementary Education, 2025)
Procrastination in elementary school students is a problem that can hinder academic development and time management skills. Procrastination can be interpreted as a delay in starting or completing a task, even though the individual is aware of the consequences. Teachers play a role in promptly identifying early signs of procrastination and intervention before the problem develops. Teachers can help students develop self-management skills that are essential for coping with procrastination. The purpose of this literature review is to review the influence of behavior contracts on the prevention of procrastination in elementary school students. A behavior contract is a written agreement between two or more parties that aims to change certain behaviors. Behavior Contracts can be used as a behavior management strategy that involves the active participation of students in setting clear goals, increasing awareness and responsibility, teaching time management, and forming the ability to plan actions. Thus, behavior contracts can be used to prevent procrastination among elementary school students.